Males and females respond differently to treatment during isolated kidney perfusion: combined effects of glucocorticoid and estradiol - Marina Vidal-dos-Santos; Marina Vidal-dos-Santos; Roberto Armstrong-Jr; Roberto Armstrong-Jr; Mayara Munhoz de Assis Ramos; Mayara Munhoz de Assis Ramos; Lucas Ferreira da Anunciação; Fernanda Yamamoto Ricardo-da-Silva; Cristiano de Jesus Correia; Petra J. Ottens; Luiz Felipe Pinho Moreira; Henri G. D. Leuvenink; et al. (Frontiers in Transplantation)
BackgroundKidney perfusion is a tool that allows organs to be assessed before transplantation. After brain death (BD), hormonal dysfunction can compromise graft quality. Hormonal treatment of donors has shown positive outcomes, and treatment during ex vivo perfusion may be advantageous. The combination of 17β-estradiol (E2) and methylprednisolone (MP) has been shown to modulate inflammation in donors. Therefore, this study aims to evaluate treatment with E2 and MP during isolated perfusion of kidneys in brain-dead male and female rats.MethodsFemale and male Wistar rats were submitted to BD and maintained for 4 h. In the same animal, the right kidney [RK—no isolated perfusion of kidney (IPK)] was removed and stored, while the left kidney (LK—with IPK) had the ureter and the renal artery cannulated and flushed with 5 ml of cold saline. The LK was then taken directly to the IPK system for 90 min. Experimental groups were performed in both male and female: IPK (without treatment) and IPK + Treat (MP and E2 added to the perfusate). Perfusion was performed with a constant pressure of 100 mmHg, using William's Medium E supplemented with HEPES, creatinine, and albumin as perfusate. Perfusate and urine were collected, and flow measurements were recorded. After IPK, the LK was stored.ResultsIL-6 was reduced in all perfused groups, regardless of treatment. In female IPK + Treat, there was a reduction in perfusion flow, followed by reduced creatinine clearance and Na+ excretion. No difference was observed in males in regards to treatment.ConclusionThe combined treatment of E2 and MP during isolated kidney perfusion compromised kidney function in females. In males, no detrimental effects were observed. These results show a sex-dependent action of the proposed treatment.